Compostos fenólicos, flavonoides e atividades biológicas do extrato etanólico e das frações da macroalga marinha parda Sargassum vulgare C. AGARDH 1820 - Baracho, Bárbara Mendes (2021)
Among marine organisms, macroalgae have been increasingly studied, as they play a fundamental role both for the ecosystem and for the economy. The brown seaweed, Sargassum vulgare, C. Agardh, 1820, was collected at Praia do Paracuru, Paracuru, Ceará, in February 2019. In laboratory, the biomass was washed, lyophilized and used for the extraction process with ethanol, whose yield was 1.52%. A part of the ethanol extract (EtOH) was reserved, and the other part was subjected to silica gel column chromatography with solvents of different polarities to obtain six fractions: hexane (Hx), dichloromethane (DCM), ethyl acetate (AcOEt), ethanolic (EtOH), methanolic (MeOH) and aqueous (H2O). The ethanol extract and its fractions were analyzed in order to quantify total phenolic compounds (TPC) and flavonoids, and to determine their biological potential, through antioxidant, phytotoxic and antimicrobial activities. The TPC results were 10.94 ± 2.08 mg EAG/g (extract) and ranged from 2.61 ± 0.06 to 38.85 ± 2.03 mg EAG/g (fractions). Flavonoid contents were 108.63 ± 3.62mg EQ/g (extract) and ranged from 1.68 ± 0.32 to 158.09 ± 6.38 mg EQ/g (fractions). The DPPH radical scavenging capacity ranged from 10.58% ± 0.91 to 16.57% ± 0.67 in the extract and from 2.55% ± 0.07 to 11.24% ± 0.99 in the fractions. The ferrous ion-chelating assay (FIC) of extracts ranged from 18.20% ± 0.00 to 22.36% ± 2.41, while this antioxidant activity varied from 4.95% ± 0.58 to 88.64% ± 1.90 in the fractions. The ferric reducing antioxidant power (FRAP) assay showed values ranging from 0.080 ± 0.013 to 0.143 ± 0.013 in the extract and from 0.061 ± 0.006 to 0.138 ± 0.009 in the fractions. The -carotene bleaching (BCB) inhibitory activity ranged from 90.76% ± 0.34 to 96.70% ± 0.67 in the extract and from 67.66% ± 1.07 to 101.87% ± 4.25 in the fractions. Phytotoxicity test on cucumber seeds (Cucumis sativus) indicated the ethanol extract as non-phytotoxic, while the fractions were able to enhance germination and root growth, with the exception of the ethyl acetate fraction considered as moderately phytotoxic. The antimicrobial assays of minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) showed values between 0.078 and 5.0 mg/mL. The results of this work revealed that the ethanol extract of S. vulgare and its fractions (Hx, DCM, AcOEt, EtOH, MeOH and H2O) possessed different biological activities with potential for both industrial and agricultural applications. Further investigation is required to elucidate the mechanisms of action responsible for these activities, and the procedures to use these compounds in products of interest.